Genomic Organization, Phylogenetic Comparison, and Differential Expression of the Nuclear Factor-Y Gene Family in Apple (Malus Domestica) - Yanjie Qu; Yaping Wang; Jun Zhu; Yugang Zhang; Hongmin Hou (Plants, 2020)
The nuclear factor Y (NF-Y) as a transcription factor plays an important role in plants growth and development, and response to stress. However, few genome-wide analyzes and functional research of the NF-Y family has been undertaken in apple (Malus domestica Borkh.) so far. In this study, we comprehensively identified the 43 MdNF-Y genes in apple, which dispersedly distributed among the three subgroups based on their sequence alignment analysis, including 11 MdNF-YAs, 22 MdNF-YBs and 10 MdNF-YCs. The members in the same subgroups had similar evolution relationships, gene structures, and conserved motifs. The gene duplication analysis suggested that all the genes were dispersed followed by 27 segmental duplication. Moreover, based on synteny analysis of MdNF-Ys with eight plant species results suggested that some ortholog genes were preserved during the evolution of these species. Cis-element analysis showed potential functions of MdNF-Ys in apple growth and development and responded to abiotic stress. Furthermore, the interaction among MdNF-Ys protein were investigated in yeast two-hybrid assays. The expression patterns of MdNF-Ys in tissue-specific response reveled divergence and might play important role in apple growth and development. Subsequently, whole MdNF-Y genes family was carried out for RT-PCR in response to five abiotic stress (ABA, drought, heat, cold, and salinity) to identify their expression patterns. Taken together, our study will provide a foundation for the further study to the molecular mechanism of apple in growing development and response to abiotic stresses.